MARKETING OPTIMIZATION IN AN EFFORT TO DEVELOP A CHICKEN MEATBALL STALL BUSINESS THROUGH A DIGITAL MARKETING APPROACH - Aulia Aulia; Agus Syam; Asmayanti Asmayanti (CV. Adiba Aisha Amira, 2025)
This research aims to identify the optimal marketing strategy in an effort to develop the Warung Bakso Ayam business using digital marketing. Digital marketing is a modern marketing approach that utilizes digital technology and the internet as the main communication channels. This research uses a qualitative research method with a descriptive approach and employs data collection techniques consisting of Observation, Interviews, and Documentation. The results of this study indicate that the Chicken Meatball Shop business, based on SWOT analysis, shows a favorable situation with the recommended SO Strategy including the optimization of Facebook and WhatsApp features, team training for the utilization of digital features, and integration with platforms such as Instagram, TikTok, and e-commerce. This strategy is expected to expand market reach and support business development to the fullest.